A new "chain" of events: polymers in the Powder Diffraction FileTM (PDF®). Issue 2 (9th April 2014) - Gates, Stacy D.; Blanton, Thomas N.; Fawcett, Timothy G.
<x content-type="archive" xml:space="preserve">Abstract</x> Developments in X-ray analysis, and advances in scientific research, have dramatically influenced the types of data now considered suitable for inclusion in the Powder Diffraction FileTM (PDF®). Initially, the PDF was geared towards the identification of unknown crystalline materials by comparison of d-spacings and peak intensities. Today, the International Centre for Diffraction Data (ICDD) maintains and continuously enhances the quality and content of the PDF database to better provide customers and scientists with a comprehensive reference source that supports their needs, and interests. The events that initially led to the inclusion of crystalline polymer data to the PDF have recently been amended to also encompass semi-crystalline and amorphous polymeric materials as well. This paper discusses the resultant updates being made to the PDF in support of this new data form, and also highlights several features and benefits of providing this data to PDF users.